Stunting dan Malnutrisi Penyebab Kelainan Email Gigi Anak dan Early Childhood Caries (ECC): Komprehensif Review - Lisa Prihastari; Djuned Prasonto; Bimo Rintoko; Hesti Witasari Jos Erry (Andalas Dental Journal, 2023)
Background: Childhood dental health is a vital component of overall well-being, with Early Childhood Caries (ECC) and defect enamel being major concerns. This article explores the intricate connection between stunting, malnutrition, and the development of defect enamel and ECC in children. Methods: Narrative review use Pubmed and Google Scholar databases with article inclusion criteria, namely research articles and reviews that discuss the relationship between enamel defects and malnutrition and ECC with malnutrition Results: Childhood malnutrition, characterized by inadequate intake of essential nutrients, poses a significant global health challenge. Stunting, a manifestation of chronic malnutrition, adversely affects physical growth and cognitive development in children. However, the link between malnutrition and dental health has not received adequate attention. This article examines the mechanisms through which malnutrition, specifically stunting, can contribute to the development of defective enamel in children. Nutritional deficiencies, particularly in calcium, vitamin D, and fluoride, are identified as key culprits in compromising enamel formation and strength. Weakening of the enamel leaves teeth vulnerable to dental caries, including ECC, which can lead to pain and long-term oral health problems. The complex relationship between malnutrition, stunting, defect enamel, and ECC calls for multifaceted solutions. Conclusion: This article highlights the importance of holistic public health initiatives, which encompass nutritional education for caregivers and improved access to dental care services for at-risk children. Interdisciplinary collaboration among healthcare professionals is emphasized to address the synergistic nature of these interconnected health challenges.